Isolation and characterization of exosomes derived from buffalo oviductal epithelial cells - K, NAHEEF; K, BRINDHA; M A, SENTHIL KUMAR T; S L, SESH P; M, PARTHIBAN; S, RANGASAMY (The Indian Journal of Animal Sciences, 2024)
In the present study, exosomes were successfully isolated from the conditioned medium of buffalo OECs cultured in vitro. Characterisation by nanoparticle analysis revealed that the size of the oviductal exosomes ranged between 40-150 nm. Imaging by Transmission electron microscopy showed that these exosomes exhibited circular/spherical morphology. The identity of isolated exosomes was further confirmed by analysing the expression of surface expressed tetraspannin markers (CD9, CD63, and CD81) by flow cytometry, and were found to be enriched with the tetraspannins analysed. As continuation of this work, further research to supplement the isolated oviductal exosomes to recreate the preimplantation physiological environment of the oviduct should be undertaken, thus improving in vitro culture conditions for buffalo embryos.